Vasoreparative dysfunction of CD34+ cells in diabetic individuals involves hypoxic desensitization and impaired autocrine/paracrine mechanisms. - Yagna P R Jarajapu; Sugata Hazra; Mark Segal; Sergio Li Calzi; Chandra Jadhao; Kevin Qian; Sayak K Mitter; Mohan K Raizada; Michael E Boulton; Maria B Grant (PLoS ONE, 2014)
We hypothesized that endothelial progenitor cells derived from individuals with diabetes would exhibit functional defects including inability to respond to hypoxia and altered paracrine/autocrine function that would impair the angiogenic potential of these cells. Circulating mononuclear cells isolated from diabetic (n = 69) and nondiabetic (n = 46) individuals were used to grow endothelial colony forming cells (ECFC), early endothelial progenitor cells (eEPCs) and isolate CD34+ cells. ECFCs and eEPCs were established from only 15% of the diabetic individuals tested thus directing our main effort toward examination of CD34+ cells. CD34+ cells were plated in basal medium to obtain cell-free conditioned medium (CM). In CM derived from CD34+ cells of diabetic individuals (diabetic-CM), the levels of stem cell factor, hepatocyte growth factor, and thrombopoietin were lower, and IL-1β and tumor necrosis factor (TNFα) levels were higher than CM derived from nondiabetic individuals (nondiabetic-CM). Hypoxia did not upregulate HIF1α in CD34+ cells of diabetic origin. Migration and proliferation of nondiabetic CD34+ cells toward diabetic-CM were lower compared to nondiabetic-CM. Attenuation of pressure-induced constriction, potentiation of bradykinin relaxation, and generation of cGMP and cAMP in arterioles were observed with nondiabetic-CM, but not with diabetic-CM. Diabetic-CM failed to induce endothelial tube formation from vascular tissue. These results suggest that diabetic subjects with microvascular complications exhibit severely limited capacity to generate ex-vivo expanded endothelial progenitor populations and that the vasoreparative dysfunction observed in diabetic CD34+ cells is due to impaired autocrine/paracrine function and reduced sensitivity to hypoxia.